Improving utilization of maximal oxygen uptake and work economy in recreational cross-country skiers with high-intensity double-poling intervals - Johansen, J.-M.; Eriksen, S.; Sunde, A.; Slettemeås, Ø. B.; Helgerud, J.; Støren, Ø. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To investigate the effect of a double-poling (DP) high-intensity aerobic interval-training (HIT) intervention performed without increasing total HIT volume. This means that regular HIT training (eg, running) was replaced by HIT DP. The aim was to explore whether this intervention could improve peak oxygen uptake in DP, the fractional utilization of maximal oxygen uptake (VO2max) in DP, oxygen cost of DP, maximal aerobic speed, and a 3-km DP time trial. Methods: Nine non-specially-DP-trained cross-country skiers (intervention group) and 9 national-level cross-country skiers (control group) were recruited. All participants were tested for VO2max in running, peak oxygen uptake in DP, oxygen cost of DP, and time-trial performance before and after a 6-wk, 3-times-per-week HIT DP intervention. The intervention group omitted all regular HIT with HIT in DP, leaving the total weekly amount of HIT unchanged. Results: Seven participants in each group completed the study. VO2max in running remained unchanged in both groups, whereas peak oxygen uptake in DP improved by 7.1% (P = .005) in the intervention group. The fractional utilization of VO2max in DP thus increased by 7.3% (P = .019), oxygen cost of DP by 9.2% (P = .047), maximal aerobic speed by 16.5% (P = .009), and time trial by 19.5% (P = .004) in the intervention group but remained unchanged in the control group. Conclusions: The results indicate that a 6-wk HIT DP intervention could be an effective model to improve DP-specific capacities, with maintenance of VO2max in running.